Cost Minimization Analysis Penggunaan Antihipertensi Candesartan Dibandingkan Amlodipin Pada Pasien JKN Rawat Jalan Di Rumah Sakit Roemani Muhammadiyah Semarang - Bella Citra Islami; Ranita Rahmaniar (Poltekkes Kemenkes Bengkulu, 2025)
Hypertension was a global health problem that required long-term therapy and caused economic burden. The cost efficiency of therapy needs to be analyzed using the Cost Minimization Analysis (CMA) approach, especially when treatment outcomes were assumed to be equivalent. This study aimed to analyze direct medical costs and the factors influencing cost differences in single antihypertensive therapy between candesartan and amlodipine among outpatient hypertensive patients covered by the National Health Insurance (JKN) at Roemani Muhammadiyah Hospital Semarang. A descriptive quantitative method with a retrospective approach was used. Samples were selected using purposive sampling from medical records of outpatient with hypertension from January 1 to December 31, 2024. The data included components of direct medical costs: doctor, administrative, laboratory, antihypertensive drug costs, and concomitant drugs costs. CMA and statistical tests were used to examine the effect of age, gender, and number of comorbidities on total direct medical costs. Of the 168 patients, 87 patients (51%) were in the candesartan groups and 81 patients (49%) were in the amlodipine group. The majority of patients were female, with 93 patients (55%) compared to 75 male patients (45%), and aged 45-64 years in both groups. Most had 1-2 types of comorbidities. The result showed that the average total direct medical cost in the candesartan group was lower (IDR213.427,00) than in amlodipine group (IDR231.305,00). Age, gender, and number of comorbidities had no significant effect on the total cost. Considering the assumed equal effectiveness and cost efficiency, candesartan was the more economical choice compared to amlodipine.